The influence of placing the patient with Alzheimer’s disease in daily-stay centre on the carer’s mental state - Wojcierowska, Agata (Nursing Problems / Problemy Pielęgniarstwa, 2008)
Introduction. The diagnosis of one of the family’s member with the Alzheimer’s disease causes necessity of adaptation to such system’s situation as it is itself. As years go by, the scope as well as the burden of the care have been increasing. Care-nursing activities are exhausting, require physical strength, psychical resistance, patience. The element of support for the carers could be the creation of daily-stay centres for people suffering from the Alzheimer’s disease. Aim. The goal of the study is to define whether the placing of the patient in a daily-stay centre has a real influence on the carer’s mental state and if the carers profit from the contact with employees of these institutions. Material and methods. Those pooled was a group composed of 35 carers of the people suffering from the Alzheimer’s disease from the centres in Bydgoszcz, Łódź and Warszawa. The survey was conducted using statistic methods and an own-authorship questionnaires. Results and conclusions. Placing the patient with the Alzheimer’s disease in a daily-stay centre has an essential influence on the carer’s mental state. Not only does the contact with the skilled staff give the opportunity to get information concerning the care and treatment of the patient, but also is an element of psychological support.